An experimental investigation of oil-water flow in a serpentine channel. (August 2020) - Der, Oguzhan; Bertola, Volfango
Highlights: The oil-water flow in a serpentine channel of millimetric size is investigated experimentally. Curved streamlines induce secondary flows enhancing mixing in comparison with straight channels. The slug length is a power-law function of the total superficial velocity. Abstract: The co-current oil-water flow in a horizontal serpentine channel is studied experimentally by high-speed imaging. Due to the channel geometry, the flow exhibits curved streamlines, which can induce secondary flows and alter the flow pattern transition boundaries in comparison with those observed in straight channels. This can have important applications in the development of microfluidic mixing devices. The serpentine channel was cut out in a black polypropylene sheet sandwiched between two transparent polypropylene sheets and bonded by selective laser welding. Different flow patterns were generated by changing independently the superficial velocities of the two fluids using a dual-drive syringe pump. Results enable the construction of a flow pattern map, which shows significant differences with the equivalent map obtained for straight microchannels.